CLUSTERING CHARACTERISTICS OF SMALL-SCALE CAPTURE FISHERIES IN PRIGI, EAST JAVA - Wahida Kartika Sari; Ledhyanne Ika Harlyan; Fuad Fuad (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2022)
Small-scale capture fisheries condition is multi gear and multispecies has an impact on increasing the pressure of fish condition. The information related to fisheries resource status is very essential in order to build sustainable fisheries management planning. This study aims to analyze the level of fishing gear productivity, clustering of fishing gear based on the number of catch fish in Prigi, East Java. These study results are expected as sustainable small-scale fisheries management recommendations. This research methods were used the analyzed of diversity by Shannon-Wiener index, catch per unit effort (CPUE) and clustering of fishing gear based on a combination between principal component analysis (PCA) and hierarchical cluster. The results showed that the composition of the catch in each fishing gear was varied. The highest diversity of fish used gillnet as fishing gear. In general, the type of fishing gear with the most catches in AFP Prigi is handline, meanwhile scoop net became the highest CPUE of fishing. Clustering of fishing gear tends to be the same with varying proximity and gillnet fishing gear is a fishing gear that tends not to group with other tools. This study resulted that the clustering of fishing gear tends not to change in the last 10 years, however the correlation between groups are dynamic and this case has an impact on the variations of catch fish and fishing gear productivity.